Bibliometric Analysis in Mapping Research with the Central Theme of Digital Content Marketing - Ulya Hasasi, Shina; Panca Rani, Meiliana; Setiawan, Adi (International Journal of Engineering, Science and Information Technology, 2025)
This research examines the development and trends of Digital Content Marketing (DCM) as a strategy to build better relationships with customers. We analyzed data from international journals published between 1988 and 2025 through a bibliometric approach, covering various elements such as digital transformation, social media, and consumer social learning. The bibliometric visualization revealed that "digital transformation" has become a central theme closely related to issues such as "social media influence" and "digital consumer engagement," suggesting a trend shift towards new topics such as "social media content marketing" in 2019-2020. These findings emphasize the importance of integrating digital and content marketing strategies to increase consumer engagement in today's digital age. The analysis found that scientific mapping and future research possibilities regarding interactive marketing can be used as recommendation variables for future researchers and as a reference for future articles.